Estudo de polimorfismos de DNA em mulheres com e sem prolapso avançado de órgãos pélvicos - Santos, Renata Gonçalves Martello dos [UNIFESP] (2017)
Objective: To verify the presence of DNA polymorphisms rs2236479 (Col18A1) and rs2862296 (LOXL-4) and its association with POP in the Brazilian population. METHODS: 532 postmenopausal women divided into POP (stage III or IV by POP-Q) and control (stage 0 or I by POP-Q) were included. Women with previous hysterectomy or other pelvic surgery were excluded. The evaluation included clinical examination and blood collection. The genetic material was analyzed by RT-PCR. The statistical analysis of the data was performed according to the type of variable, using the chi-square test, mean and standard deviation, and median and 25th and 75th percentiles. For comparison between groups, the t test -Student for two independent samples and the Mann-Whitney test. The verification of the association between genotypes and the presence of prolapse was estimated by the odds ratio (OR) and respective 95% confidence intervals (95% CI) using binary logistic regression models. Results: A greater proportion of the genotypes with at least one polymorphic allele (AG and GG) of the LOXL-4 gene was verified in the control group compared to the POP group (73.2% and 67.3%, respectively, p = 0.465 ). As for the Col8A1 gene, a higher percentage of GA genotype was found in the control group (50.2% and 44.2%, respectively) and a higher number of women with POP and both polymorphic alleles (AA) (17.5% and 15.4% respectively), non-statistically significant results (p = 0.556). No associations were observed between presence of polymorphisms and POP. However, in the group of women homozygous for the polymorphic allele, both for LOXL-4 (GG) and Col18A1 (AA), OR less than 1 (OR = 0.84, 95% CI (0.47, 1.50 ) and (OR = 0.91, 95% CI (0.50, 1.65), respectively, suggest that these genotypes may be protective factors for POPs. In addition, the variables age, higher number of pregnancies, normal and presence of family history of POP were associated with the presence of dysfunction. Conclusion: There was no association between the presence of polymorphisms rs2862296, of the LOXL-4 gene, and rs2236479, of the Col18A1 mole, and the development of genital prolapse degrees III or IV in this sample of patients.